Comparison of Domestic and Foreign Studies on the Impact of Built Environment on Public Health and Its Implications - Li Shan; Zhang Lin; Li Jianjun; Chen Tingting; Chen Jintang (Redai dili, 2024)
Built environments have complex effects on the public's physical and mental health. Revealing the mechanisms and pathways through which the urban built environment influences public health can provide a basis for optimizing built environments. This helps avoid issues, such as environmental pollution, lack of social interaction, and insufficient physical activity, ultimately contributing to the enhancement of public health. Western academia has a more established foundation for research, whereas domestic endeavors are currently in the exploratory phase. A comparative analysis of relevant domestic and international studies can help elucidate the developmental trajectory of research in this field, identify common issues and characteristics, and guide the direction for advancing domestic research. Therefore, based on the Web of Science and China National Knowledge Infrastructure databases, this study systematically reviewed 658 English and Chinese studies published from 2000 to 2022 in the fields of urban and rural planning, geographic sciences, health medicine, and environmental psychology, focusing on the impact of the built environment on public health. Utilizing "Citespace" software, this study conducted a quantitative analysis and systematic review of the theoretical framework, study topics, and emerging trends in the research. The findings revealed disparities between Western and Chinese academies in terms of theoretical innovation, study groups, and research content. Specifically, international studies have pioneered theoretical perspectives, such as social welfare and environmental justice. Guided by these theories, researchers have explored the mechanisms through which the built environment affects public health in diverse population groups. Although domestic studies exhibit a relative lack of theoretical innovation, their primary focus has been the introduction and empirical application of Western theories in the Chinese context. These studies often concentrate on the transmission paths of the impacts on the older and women groups through static empirical evidence, lacking dynamism in their approaches. Furthermore, drawing upon the previously stated theoretical underpinnings, methodological approach, and research content, this paper summarized the analytical framework of "Built Environment Elements, Mediated Impacts, and Public Health." It meticulously examined the differential effects of three spatial elements—green space, land use, and road traffic—on public health. This study provides a detailed analysis of the mechanisms involved, highlighting the ecological and psychological benefits arising from exposure to and interactions with green spaces. It also analyzes how judiciously designed and compact land use patterns shape travel preferences, reduce travel distances, mitigate reliance on motor vehicles, and enhance the frequency of individual activities. Furthermore, the study outlines the ramifications for optimizing the road network system and transitioning travel modes to ameliorate traffic pollution, alleviate traffic pressure, and mitigate pedestrian injuries, among other variables. The purpose of this study was to systematically comprehend the current status and disparities in domestic and international research concerning the impact of the built environment on public health and to explore a series of health issues triggered by the built environment from the perspective of urban planning, with the hope of promoting health geography in China, offering guidance for future academic directions, and prompting local management authorities to formulate precision policies addressing public health challenges.